Upregulation of miRna-143, -145, -192, and -194 in esophageal epithelial cells upon acidic bile salt stimulation. Issue 6 (1st August 2014) - Bus, P.; Siersema, P. D.; Verbeek, R. E.; van Baal, J. W. P. M.
Summary: B arrett's esophagus (BE ) is a metaplastic condition of the distal esophagus that occurs because of chronic gastroesophageal reflux. Previous studies have identified BE -specific microRNAs (miRNAs ) in comparison with normal squamous epithelium (SQ ). We hypothesized that BE -specific miRNAs could be induced in esophageal SQ cells by exposure to acid and/or bile salts. We aimed to determine whether BE -specific miRNAs are upregulated in an esophageal SQ cell line (Het-1A ) in an environment with acid and/or bile salts and whether this is nuclear factor-κB (NF-κB ) dependent. Acid and/or bile salt incubations were performed in Het-1A cells. Experiments were performed with or without inhibiting the NF-κB pathway. Quantitative reverse transcriptase polymerase chain reaction was performed to determine expression of miRNA -143, -145, -192, -194, cyclo-oxygenase-2 (COX2 ), mucin 2 (MUC2 ), and sex determining region Y -box 9. For validation, we determined levels of these miRNAs in biopsies from patients with reflux esophagitis and normal SQ . Significantly increased expression levels of miRNA -143 (2.7-fold), -145 (2.6-fold), -192 (2.0-fold), -194 (2.2-fold), COX2, MUC2, and sex determining region Y -box 9 were found upon acidic bile salt incubation, but not upon acid or bile salt alone. NF -κB pathway inhibition significantly decreased miRNA -143, -192, -194, COX2, and MUC2 expression. Additionally, miRNA -143, -145 and -194 expression was increased in reflux esophagitis biopsies compared with normal SQ, but no changes were found in miRNA -192 expression. Our findings suggest that upregulation of BE -specific miRNAs by acidic bile may be an early event in the transition of SQ to BE and that their expression is partly regulated by the NF -κB pathway.